National taxation, fiscal federalism and global taxation - Robin Boadway (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper considers lessons from the practice of fiscal federalism for guidance on new approaches to development finance. Despite the fact that inter-regional redistribution in a federation relies on a central government with strong fiscal powers, the form of that redistribution can be used as a benchmark for international development assistance financing. In a federation, finance for less-developed regions takes the form of equalizing transfers to sub-national governments. The objective of these transfers is to enable sub-national governments to provide comparable levels of public services at comparable tax rates, called fiscal equity, leaving them discretion to implement interpersonal redistribution schemes within their jurisdictions. This same principle of assuming that national governments rather than donor nations are responsible for vertical equity within their borders leads to the view that the ideal form of development assistance is a system of equalizing inter-nation transfers intended to enhance fiscal equity.
Keywords: H7; F35; 330; fiscal federalism; equalization; development finance; Finanzföderalismus; Entwicklungsfinanzierung